Ethnomathematics: Mathematical Activities of Hand-drawn Batik Craftsmen Community in Giriloyo, Yogyakarta, Indonesia - Abdullah, Ahmad Anis; Richardo , Rino; Mubarok , Muhammad Najib; Bayu , Widya Sekar (Journal of Education Culture and Society, 2025)
Aim. This study is an ethnomathematical study that aims to describe and interpret the Mathematical Activities of the Hand-drawn Batik Craftsmen Community located in Giriloyo, Yogyakarta, IndonesiaMethods. This report utilized an ethnographic method, with data being obtained through observation, interviews, documentation, and Focus Group Discussion (FGD). The subjects of the study were a group of five hand-drawn batik craftsmen from Giriloyo, Yogyakarta, Indonesia. A literature review on batik was utilized to complement the results obtained through the observations and interviews. Following that, the data was analysed qualitatively.Results. From the data analysis, it was found that this community engaged in mathematical activities during hand-drawn batik production which include measuring, pattern-making, and estimating. This is reflected in: first, their method of taking measurements and using units to arrange the batik motifs; second, pattern-making that can be seen in batik motifs, especially geometric motifs; and third, estimation activities observed in determining the price of a piece of hand-drawn batik.Conclusions. The traditional activity of making batik with canting is culturally rich in values and philosophies that need to be preserved. Ethno-mathematical research on the activities of the hand-drawn batik community can yield products applicable to school lessons.